2019
DOI: 10.1523/jneurosci.3107-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Orchestrates Self-Organization of Neurons within a Columnar Unit in the Drosophila Medulla

Abstract: Columnar structure is a basic unit of the brain, but the mechanism underlying its development remains largely unknown. The medulla, the largest ganglion of the Drosophila melanogaster visual center, provides a unique opportunity to reveal the mechanisms of 3D organization of the columns. In this study, using N-cadherin (Ncad) as a marker, we reveal the donut-like columnar structures along the 2D layer in the larval medulla that evolves to form three distinct layers in pupal development. Column formation is ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 58 publications
(99 reference statements)
0
49
0
Order By: Relevance
“…In our previous study, we showed that R8, R7, and Mi1 are the core columnar neurons that contribute to column formation during the L3 larval stage (Trush et al, 2019). L1-L5 lamina neurons also project to columns at the end of the L3 larval stage.…”
Section: R8 R7 Mi1 and L1-l5 Neurons Play Essential Roles In Colummentioning
confidence: 92%
See 4 more Smart Citations
“…In our previous study, we showed that R8, R7, and Mi1 are the core columnar neurons that contribute to column formation during the L3 larval stage (Trush et al, 2019). L1-L5 lamina neurons also project to columns at the end of the L3 larval stage.…”
Section: R8 R7 Mi1 and L1-l5 Neurons Play Essential Roles In Colummentioning
confidence: 92%
“…In our previous study, we showed that N-cadherin (Ncad) clearly labels medulla columns during development (Liu et al, 2020;Trush et al, 2019). Fmi belongs to the cadherin superfamily and is involved in Wnt/PCP signaling (Usui et al, 1999).…”
Section: Fmi Can Be Used To Visualize Developing Columnsmentioning
confidence: 99%
See 3 more Smart Citations